Odpowiedzi

  • Użytkownik Zadane
2010-03-25T20:21:01+01:00
-7+3y+9+2y = 5y +2
-5+4y-y-7x-9y = -6y - 7x -5
4x+5-x-4+x-3x = x +5
0,5a-2a+9-0,5a-11,5 = -2a - 2,5
-14k+9k-13+k+3+4k = -10
-3k+2m+5m-7+k-m = -2k + 6m - 7
2x-4+3x-2 = 5x - 6
x-3y-2x+6y = -x + 3y
2y-5-3y-4-8y+9 = -9y
2010-03-25T20:30:17+01:00
-7+3y+9+2y = 2+5y
-5+4y-y-7x-9y = -5-6y-7x
4x+5-x-4+x-3x = x+1
0,5a-2a+9-0,5a-11,5 = -2a-2,5
-14k+9k-13+k+3+4k = -10
-3k+2m+5m-7+k-m = -2k+6m-7
2x-4+3x-2 = 5x-6
x-3y-2x+6y = -x+3y
2y-5-3y-4-8y+9 = -9y